Quality-of-life experiences from the perspective of patients receiving haemodialysis for chronic renal failure - Louis F. Small (AOSIS, 2010)
This study describes the experiences of patients receiving haemodialysis for chronic renal failure at the only dialysis centre in Windhoek, Namibia. A qualitative, explorative and descriptive design was used. Data were collected by means of in-depth interviews and analysed using Tesch's process.Four themes emerged from the data, relating to (1) financial constraints, (2) loss of independence and spontaneous activities, (3) strain on relationships and (4) feelings of significant physiological changes and weakness. Based on the results, recommendations were submitted for psychosocial support and the establishment of support groups. Opsomming Hierdie studie beskryf die ervarings van pasiënte wat gehemodialiseer word vir chroniese nierversaking in die enigste dialise-eenheid in Windhoek. ŉ Kwalitatiewe, verkennende en beskrywende studie is gedoen. Die data is deur middel van diepte-onderhoude ingesamel, waarna die data aan die hand van Tesch se metode geanaliseer is. Daar het vier temas uit die studie na vore gekom (1) finansiële beperkings, (2) verlies van onafhanklikheid en spontane aktiwiteite, (3) druk in verhoudings en (4) gewaarwordings van beduidende fisiologiese veranderinge en swakheid.Na aanleiding van hierdie bevindings is die daarstel van psigososiale ondersteuning asook ondersteuningsgroepe aanbeveel.